The functional biogeography of species: biogeographical species roles of birds in Wallacea and the West Indies - Carstensen, Daniel W.; Dalsgaard, Bo; Svenning, Jens-Christian; Rahbek, Carsten; Fjeldså, Jon; Sutherland, William J.; Olesen, Jens M. (Ecography (Copenhagen), 2013)
Biogeographical systems can be analyzed as networks of species and geographical units. Within such a biogeographical network, individual species may differ fundamentally in their linkage pattern, and therefore hold different topological roles. To advance our understanding of the relationship between species traits and large-scale species distribution patterns in archipelagos, we use a network approach to classify birds as one of four biogeographical species roles: peripherals, connectors, module hubs, and network hubs. These roles are based upon the position of species within the modular network of islands and species in Wallacea and the West Indies. We test whether species traits – including habitat requirements, altitudinal range-span, feeding guild, trophic level, and body length – correlate with species roles. In both archipelagos, habitat requirements, altitudinal range-span and body length show strong relations to species roles. In particular, species that occupy coastal- and open habitats, as well as habitat generalists, show higher proportions of connectors and network hubs and thus tend to span several biogeographical modules (i.e. subregions). Likewise, large body size and a wide altitudinal range-span are related to a wide distribution on many islands and across several biogeographical modules. On the other hand, species restricted to interior forest are mainly characterized as peripherals and, thus, have narrow and localized distributions within biogeographical modules rather than across the archipelago-wide network. These results suggest that the ecological amplitude of a species is highly related to its geographical distribution within and across biogeographical subregions and furthermore supports the idea that large-scale species distributions relate to distributions at the local community level. We finally discuss how our biogeographical species roles may correspond to the stages of the taxon cycle and other prominent theories of species assembly.